PERBANDINGAN PREDIKSI HASIL SEDIMEN MENGGUNAKAN PENDEKATAN MODEL UNIVERSAL SOIL LOSS EQUATION DENGAN PENGUKURAN LANGSUNG (Comparison of sediment yield from prediction using Universal Soil Loss Equation with direct measurement) - Diah Auliyani; Wahyu Wisnu Wijaya (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2017)
Low level of sedimentation is a success indicator of watershed management. Measurement of sedimentation can be conducted directly or through erosion prediction approach. This research aimed to compare sediment yield from prediction by USLE erosion approach using three types formulations of rainfall erosivity with direct measurement. The field data were collected during 2015 in Lowereng Sub Watershed, Sempor District of Kebumen Regency. The slope steepness was derived from ASTER Global Digital Elevation Model and land cover was obtained from World View 2012. Three methods for estimating rainfall erosivity were Utomo and Mahmud, Bols, and Lenvain equations. The USLE applied for every land unit. By considering Sediment Delivery Ratio (SDR), the predicted soil erosion from USLE was converted into sediment yield. The direct measurement of sediment yield was conducted by taking suspended sediment in the outlet of sub watershed. This research indicates that the predicted sediment yield calculated using USLE approach was higher than the direct measurement. The predicted sediment yield using Lenvain’s equation was 3.49 ton/ha (196%), which was the closest to the direct measurement (1.18 ton/ha).